Influence of Wastewater Treatment Technologies on Virus Removal Under a Bibliometric-Statistical Analysis - Villamar-Ayala, C; Plaza-Garrido, A (Elsevier Ltd, 2022)
Viruses (e.g., SARS-CoV-2) are discharged into surface water bodies or agricultural irrigation from treated municipal/domestic wastewater. Therefore, this study aimed to evaluate the viral removal from wastewater treatment technologies, also considering wastewater physicochemical properties based on a bibliometric-statistical review. A preliminary bibliometric analysis (keywords co-occurrence) using VOS viewer (n = 698 scientific publications) was established. Moreover, systematic constraining criteria (1983–2021) limiting the statistical study to 93 scientific publications were carried out. Variance Analysis (ANOVA-2 ways) and Principal Component Analysis (PCA) were used to identify the most influential wastewater treatment typology and parameters affecting viral removal. Bibliometric results showed that at least 25% of the studies on viral removal from wastewater corresponded to the last 2 years. Therefore, SARS-CoV-2 was approached in a particular way. Thus, more than 15 viruses and/or genotypes and more than 20 specific/non-specific technologies for viral removal were statistically analyzed. Results did not report significant differences (p < 0.05) of Log Removal Virus (LRV) between specific (e.g., MBR, chlorination) and non-specific (e.g., activated sludge, anaerobic digestion) technologies. However, MBR (specific) and anaerobic digestion (non-specific) reported the highest viral removal efficiencies. SARS-CoV-2 has been reported to be removed by specific and non-specific technologies, but it is not conclusive. Preliminary statistical approximations establish that the physicochemical parameters (COD, TSS, pH) from wastewater could influence the viral removal. Future challenges should focus on operational improvements, new technology development, and regulation (recycling, discharge) assuming potential risks (human, environment). © 2022 Elsevier Ltd